Partsisipasi Masyarakat Dalam Perencanaan Program Nasional Pemberdayaan Masyarakat Mandiri Pedesaan (PNPM-MP) (Suatu Studi Di Desa Tawa Bacan Tengah Kabupaten Halmahera Selatan) - Molle, Frensi; Sondakh, Telly; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The purpose of this study to determine the Community Participation in PlanningNational Program of Rural Community Empowerment (PNPM-MP) In the village of Tawa CentralBacan District South Halmahera as a general purpose of the National Program for CommunityEmpowerment in Rural Areas is to improve the livelihoods and employment opportunities of thepoor in rural areas. To determine the Public Participation in Planning National Program forCommunity Empowerment Rural (PNPM-MP), the researchers refer to the theories Ericson (inSlamet, 1994: 89) forms of community participation in development is divided into three stages,namely: participation in planning, participation in the implementation of, and participation inpemanfaatan.Dengan using qualitative method where the researcher as a key instrumentconsisting of 6 informants.Public participation in the planning of the National Program of Rural CommunityEmpowerment (PNPM-MP) in the village of Tawa not running optimally. Because according tothe reality in the field is only part of the population that participated in the form of thoughts orsuggestions and input in the preparation of development programs or the National Program forCommunity Empowerment of Rural .; Public participation in the implementation phase of menmore active role in the implementation of self-help in the form of energy, thoughts, and material.While women prefer the affairs of the household, as well as the community's participation in thedevelopment stage of utilization of the National Program for Community Empowerment is notgroomed properly, so it is not proper to be used again by the public.To achieve the general objectives of the National Program of Rural CommunityEmpowerment (PNPM-MP), the village government should give attention to disseminating theprogram to the public by calling or inviting the public to participate in the planning stage. Societyas a target group of the National Program for Community Empowerment Rural, it is expectedberperanaktif in the implementation of both men and women. Because basically the purpose ofPNPM-MP is to improve the lives of local people. As well as the village government needs toprovide a good understanding of the community in the maintenance of the results of developmentof the National Program for Community Empowerment or village government needs to create amaintenance team is the result of development of National Program of Rural Peoples, Mandiri(PNPM-MP) in the village of Tawa.Keywords: Paritsipasi Society, the National Program for Community Empowerment Rural.